Characterization of Temperature Response of Asymmetric Tapered-Plastic Optical Fiber-Mach Zehnder Interferometer - Ian Yulianti; Ngurah Made Darma Putra; Fianti Fianti; Abu Sahmah Mohd Supaat; Helvi Rumiana; Siti Maimanah; Kukuh Eka Kurniansyah (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Temperature measurement is important in various applications; therefore, various temperature sensors have been developed. Due to its advantages, many optical fiber-based temperature sensors have been proposed. The wavelength modulation-based optical sensor is interesting due to high accuracy. However, the complex fabrication process and high cost limit the advantages of the sensors. Therefore, we proposed a simple and low-cost Mach Zehnder interferometer (MZI) sensor using step-index plastic optical fiber (SI-POF). Performance characterization of the sensor to temperature variation is presented. The sensor consists of two tapers at several distances, forming an interferometer. The first taper was designed to be steep to allow excitation of cladding modes, while the second taper was gradual to suppress power loss. Characterizations were done in terms of sensitivity, hysteresis, and repeatability by analyzing the output spectrums recorded by the spectrometer at various environment temperatures, 35oC to 85oC, with an increment of 10oC. The results showed that the sensor has a sensitivity of 0.0431 nm/oC and a correlation coefficient of 0.9965. Hysteresis of 6.9Ã—10-3 was observed. In terms of repeatability, the sensor shows a maximum deviation, ±3oC, which was mainly resulted from the fluctuation of the oven temperature. Despite its high deviation, the sensor has advantages of simple fabrication, low cost, robust, and low power loss, which make it a good candidate for temperature sensors.